Effect of Parkia Biglobosa (JACQ) G. Don. Pod Extracts on its Seed Germination and Seedling Development. - Adeyemi, Oreoluwa; S. OLORUNMAIYE, Kehinde; O. OGUNSOLA, Kike (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The pod extracts at different concentrations influenced the seed germination and seedling vegetative growth of twenty-six different Parkiabiglobosa(JACQ) G. Don Samples. Aqueous Parkia pod extracts of various concentrations (5, 10, 15 and 20g in 100ml of water) were used for the planting of the Parkia seeds and water as control. Significant (at p=0.05) reduction was observed in concentration of 20g of Parkia pod. The seed germination, epicotyl and hypocotyl lengths of the seedlings of the different Parkia trees exhibited varying responses to the extracts at various concentrations among the twenty-six Parkia biglobosa tree seeds used for the germination study within the three weeks of the experiment. The retardation in the seedlings vegetative growth was suspected to influence by the allelopathic components in the pod extracts. The varied responses of the Parkia seedlings to these extract concentrations were assumed to be either from the pod used which were selected from all the tree samples or that the seedlings were sensitive to an allelophatic chemicals of their own pod extracts or to other pods extracts.